Persepsi Terapis Wicara tentang penggunaan Evidence-Based Practice (EBP) dalam pemilihan Metode Terapi Afasia - Widiastuti, Arfian; Siswanto, Arif (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Abstract Background: In line with the increasing number of speech therapists, services for stroke patients with language disorders are increasingly fulfilled. On the other hand, the application of various therapeutic methods in aphasia cases is also varied but it is not so clear whether the selection of these methods also uses the principles of evidence-based practice (EBP). Objectives: This study aims to determine the perception of speech therapists regarding the use of EBP in the selection of therapy methods for aphasia patients. Methods: Descriptive quantitative research design with a sample size of 44 people using purposive sampling. Results: Most speech therapists believe systematic review will be able to provide the best efficacy and EBP helps in the process of determining goals and selecting interventions for aphasia patients. The higher the frequency of using EBP literature, the better the application to the therapy method. Conclusion: The use of EBP is still weak in the selection of aphasia methods by most speech therapists. There needs to be strategic steps from the professional association to further socialize EBP at the clinical level. Keywords: Perception, EBP, Therapy Method, Aphasia.